Efficacy of Combined Use of PELNAC and Platelet-rich Plasma in Promoting Wound Healing - Hiroshi Fujimaki, MD, PhD; Hajime Matsumine, MD, PhD; Yuki Hasegawa, MD, PhD; Yosuke Niimi, MD, PhD; Hiroyuki Sakurai, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Background:. Artificial dermis is useful for treating full-thickness skin defects but requires a long time to form dermis-like granulation tissue. This study investigated whether platelet-rich plasma (PRP) combined with PELNAC, a collagen-based artificial dermis, promotes wound healing and examined the underlying mechanism. Methods:. Two 1-cm² full-thickness skin defects were created in 8-week-old male nude rats (n = 8). One defect received saline-impregnated PELNAC (control group); the other received PRP-impregnated PELNAC (combination group). Cytokine levels in PRP were measured. Wound area measurements and histological and immunohistochemical evaluations (transforming growth factor-β1 [TGF-β1], vascular endothelial growth factor [VEGF], α-smooth muscle actin, and von Willebrand factor) were performed on day 14. Results:. Compared with the control group, the combination group showed a significantly reduced wound area (32.4 ± 14.89 versus 68.3 ± 14.9 mm², P < 0.001) and increased dermis-like granulation tissue thickness (947 ± 219 versus 448 ± 165 μm, P < 0.001). Expression of TGF-β1 (8.9% ± 1.7% versus 4.2% ± 1.2%, P < 0.0001) and VEGF (4.4% ± 1.2% versus 1.9% ± 0.5%, P < 0.0001) was significantly higher in the combination group, whereas α-smooth muscle actin–positive cells and von Willebrand factor–positive blood vessels showed no significant differences. Conclusions:. The combined use of PELNAC and PRP accelerated dermis-like granulation tissue formation through increased expression of VEGF and transforming growth factor-β1, significantly improving wound healing. This combination therapy could be easily applied in clinical practice and may contribute to shortening healing times for deep dermal defects.